Dual mechanism design to enhance bone formation by overexpressed SDF-1 ADSCs in magnesium doped calcium phosphate scaffolds. (October 2021) - Sun, Zhaoqi; Lin, Chao; Wu, Kailiu; Wang, Mingyi
Graphical abstract: Highlights: Dual mechanism was designed to combine gene therapy and tissue inductive scaffolds. Migration and homing of endogenous cells were enhanced by SDF-1 transduction. Magnesium doped calcium phosphate (MCPC) scaffold is pro-osteogenic. SDF-1 transduction combined with MCPC scaffold is effective in bone regeneration. Abstract: Background: SDF-1/CXCR4 axis plays a critical role in the mobilization and regeneration of host-derived cells. Little is known around the role of SDF-1 gene on bone regeneration. This study was conceptualized to create a 2-in-1 strategy by identifying potential role of SDF-1 on promoting endogenous osteoblast migration and synergizing with magnesium doped calcium phosphate scaffold (MCPC) on osteogenic differentiation. Method: ADSCs were transfected with Lenti-SDF-1. Cell proliferation, osteogenic gene expression and ALP/ARS staining were investigated. Osteoblast migration was studied. MCPC construct was employed as carrier of Lenti-SDF-1 ADSCs. Osteogenic gene expressions of BMSCs were determined in MCPC + ADSCs medium. MCPC + Lenti-SDF-1 ADSCs scaffolds were implanted into rats and bone regeneration efficacy was evaluated by micro-CT and histological analysis. Result: SDF-1 transduction neither impacted ADSCs' proliferation, nor osteogenic differentiation. Lenti-SDF-1 ADSCs promoted migration of BMSCs/osteoblasts. MCPC facilitated osteogenic differentiation of BMSCs. Bone formation was significantly increased in MCPC + Lenti-SDF-1 group. Conclusion: Overexpressed SDF-1 gene promotes the homing of endogenous osteoblasts. MCPC + Lenti-SDF-1 facilitated robust in situ bone regeneration via dual mechanisms by recruiting endogenous BMSCs' and enhancing homing cell's differentiation. This advanced design combines gene therapy and osteoinductive tissue scaffolds, which is proved to be a promising strategy to achieve satisfied clinical bone repair efficacy.